An Assessment of West Nile and Usutu Viruses’ Seroprevalence in Hospitalized Patients: A Preliminary Study on Flavivirus Exposure in Eastern Romania - Luciana Alexandra Crivei; Andrei Vata; Danut Teodor; Daniela Porea; Andreea Paula Cozma; Adriana Anita; Luanda Elena Oslobanu; Serban Morosan; Gheorghe Savuta (Pathogens, 2024)
WNV and USUV are closely related epornitic flaviviruses transmitted by Culex mosquitoes which can cause febrile and neurodegenerative disease in humans. The impact of both viruses on public health has increased in the recent decades. Aim: The aim of the study was to evaluate the seroprevalence of WNV and USUV in hospitalized patients from eastern Romania who did not show symptoms corresponding to the case definition. Methods: Human blood samples from the hospitalized patients were collected in 2015 and from April to September 2019 in Iasi County, Romania. The samples were screened by ELISA for anti-WNV IgG, IgM, and anti-USUV IgG antibodies. Results: A cumulative seroprevalence of 3.4% was recorded for anti-WNV IgG antibodies and 9.1% for anti-WNV IgM. No sample was positive for anti-USUV antibodies. Conclusion: The cumulative seroprevalence observed provides support for the consideration of WNV as being endemic in the east of Romania. The absence of anti-USUV antibodies may be related to cross-reactivity and cohort size, thus, USUV should be considered in clinical practice and become an objective for active surveillance in Romania.